When Judicial Protection Excludes: Parenthood, Disability, and Human Rights in Dispute (Palimpsesto, 2025)
This article critically analyzes the judicial and institutional practices experienced by parents with intellectual disabilities in Chile, within the framework of legal proceedings related to child custody. Using a qualitative single-case study approach, 171 judicial and intervention program documents were examined, along with six interviews conducted with key stakeholders. The analysis revealed a systematic absence of reasonable accommodations, assessments based on normative models lacking a rights-based perspective, and measures reinforcing discrimination through a punitive approach toward disability. The article concludes that institutional practices reproduce structural exclusions and recommends a shift towards an inclusive paradigm, emphasizing personalized support and intersectoral strategies to ensure the right to family life in conditions of equality and dignity.